Highly selective organic transistor biosensor with inkjet printed graphene oxide support system. Issue 19 (26th April 2017) - Lee, Dong-Hoon; Cho, Hee-Sang; Han, Dawoon; Chand, Rohit; Yoon, Tae-Jong; Kim, Yong-Sang
Abstract : The synthesized graphene oxide ink was printed on FET biosensor for specific bio-sensing of DNA and CTCs. Abstract : Most of the reported field effect transistors (FETs) fall short of a general method to uniquely specify and detect a target analyte. For this reason, we propose a pentacene-based FET with a graphene oxide support system (GOSS), composed of functionalized graphene oxide (GO) ink. The GOSS with a specific moiety group to capture the biomaterial of interest was inkjet printed on the pentacene FET. It provided modular receptor sites on the surface of pentacene, without alteration of the device. To evaluate the performance of a GOSS-pentacene FET biosensor, we detected the artificial DNA and circulating tumor cells as a proof-of-concept. The mobility of the FET dramatically changed upon capturing the target biomolecule on the GOSS. The FET exhibited high selectivity with 0.1 pmoles of the target DNA and a few cancer cells per detection volume. This study suggests a valuable sensor for medical diagnosis that can be mass produced effortlessly at low-cost.